Ensino de astronomia básica para estudantes da EJA - SILVA, William Danilo da (2023)
The teaching and learning process, in the context of Science teaching, in Youth and Adult Education (YAE) classes, was addressed in this work, which aimed to discuss to what extent the methodologies applied with students, have been (or not) successful; Its aim was also to analyze, based on the participants' responses, the quality of the material used during classes in this subject. To this end, action research was taken as a methodology, from a perspective, where, in addition to collecting data to solve the problem, an approach was made with the participants, YAE students, applying questionnaires, and in order to assess their level of knowledge on the topic of Astronomy. The responses were then discussed in the light of studies such as those by Dittz (2021), Ferroni (2007), Quintanilha (2021), Silva (2019), among others, in addition to promoting eight meetings, which themes were worked based on the topic, and the product was constructed, an Educational BasicTeach to EJA students. It was concluded that, as part of the basic school curriculum, the subject Science must be worked from a perspective of meaning, selecting carefully themes such as Astronomy, in line with an adequate choice of teaching materials that enable students to make the necessary articulation between the contents worked on and everyday aspects.